2017
DOI: 10.1017/s1478951516000882
|View full text |Cite
|
Sign up to set email alerts
|

Aligning guidelines and medical practice: Literature review on pediatric palliative care guidelines

Abstract: Our results indicate that a critical assessment of both the research guidelines and medical practice is required in order to promote timely implementation of PPC for pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 79 publications
0
37
0
Order By: Relevance
“…51,52 Multiple studies have cited conceptual confusion between PC and hospice or EOL care, as well as the stigma of hopelessness associated with PC, as significant obstacles to early PC discussions. 6,[53][54][55][56] The International Classification of Disease coding system considers hospice and end-of-life care as synonymous with palliative care, and US clinicians are instructed to bill these services identically. 57 There are even definitional inconsistencies between and among PC guidelines of what palliative care constitutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 Multiple studies have cited conceptual confusion between PC and hospice or EOL care, as well as the stigma of hopelessness associated with PC, as significant obstacles to early PC discussions. 6,[53][54][55][56] The International Classification of Disease coding system considers hospice and end-of-life care as synonymous with palliative care, and US clinicians are instructed to bill these services identically. 57 There are even definitional inconsistencies between and among PC guidelines of what palliative care constitutes.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) released a seminal report, titled Cancer Pain Relief and Palliative Care in Children , in which it recommended that palliative care (PC) for children with cancer ought to begin at diagnosis, irrespective of prognosis . Other international health organizations—the American Academy of Pediatrics (AAP), Institute of Medicine (IOM), European Association for Palliative Care (EAPC), and the Royal College of Paediatrics and Child Health (RCPCH)—have all since adopted a similar recommendation . These calls for earlier PC are grounded in evidence of an unmet need: the high illness burden and degree of suffering are well established among children with cancer .…”
Section: Introductionmentioning
confidence: 99%
“…PC is associated with improved quality of life, and previous studies have found children with cancer and their families want PC to be integrated early in the illness timeline . With mounting evidence, PC is increasingly recommended for pediatric oncology patients …”
Section: Introductionmentioning
confidence: 99%
“…3 With mounting evidence, PC is increasingly recommended for pediatric oncology patients. [4][5][6] Most PC services for children with cancer are rendered in the inpatient setting. 7 The American Academy of Pediatrics recommends consideration of PC from diagnosis in children with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several barriers to adequate implementation and sufficient provision of PPC have been identified in the literature, such as, organizational, cultural and economic obstacles 1 . Various scholars have also focused on the problem of conceptual confusion and in particular, on the lack of a shared understanding of PC [2][3][4][5][6] . They argue that good PC provision necessitates such a common understanding.…”
Section: Introductionmentioning
confidence: 99%